Plant composition and structure of two post-livestock areas of Tamaulipan thornscrub, Mexico - Pequeño Ledezma, Miguel Angel; Alanís Rodríguez, Eduardo; Molina Guerra, Víctor Manuel; Mora Olivo, Arturo; Alcalá Rojas, Alejandro G.; Martínez Ávalos, José Guadalupe; Garza Ocañas, Fortunato (2018)
Abstract Background: The composition, structure and biological diversity of two regenerated areas after livestock activities in a Tamaulipan thornscrub vegetation from Northeast Mexico were evaluated. The regeneration of each area was evaluated with the establishment of 12 sampling sites of 50m2. From the data obtained ecological indexes such as: Importance Value Index and Diversity (alpha and beta) were evaluated. Results: A total of 17 families, 40 genera and 42 species were registered, the most representative family was Fabaceae with 11 spp. The intensive livestock area had 36 species; a Margalef index of 4.44 and a 1.24 Shannon index, while the extensive livestock area had 32 species, a Margalef index of 4.24 and a 2.16 Shannon index. The communities evaluated have a (48%) mean similarity. Conclusions: 1) Regenerated communities after livestock use showed higher richness of species and alpha diversity. 2) Evaluated communities have a mean similarity of (48%). 3) Even after 25 years of regeneration the most dominant species was Cenchrus ciliaris that is used for cattle forage. Keywords: Diversity, Livestock, Mexican scrubs, Plant regeneration, Shannon index